Current induced domain wall motion in antiferromagnetically coupled (Co70Fe30/Pd) multilayer nanowires - Meng, Zhaoliang (2017)
We investigate the current induced domain wall (DW) motion in the ultrathin CoFe/Pd multilayer based synthetically antiferromagnetic (SAF) structure nanowires by anomalous Hall effect measurement. The threshold current density (Jth) for the DW displacement decreases and the DW velocity (v) increases accordingly with the exchange coupling Jex between the top and bottom ferromagnetic CoFe/Pd multilayers. The lowest Jth = 9.3 x 10^10 A/m2 and a maximum v = 150 m/s with J = 1.5 x 10^12 A/m2 are achieved due to the exchange coupling torque (ECT) generated in the SAF structure. The strength of ECT is dependent on both of Jex and the strong spin-orbit torque mainly generated by Ta layer.